Boron‐Induced Electronic‐Structure Reformation of CoP Nanoparticles Drives Enhanced pH‐Universal Hydrogen Evolution. (23rd January 2020) - Cao, Erping; Chen, Zhimin; Wu, Hao; Yu, Peng; Wang, Ying; Xiao, Fei; Chen, Shuo; Du, Shichao; Xie, Ying; Wu, Yiqun; Ren, Zhiyu
Abstract: Even though transition‐metal phosphides (TMPs) have been developed as promising alternatives to Pt catalyst for the hydrogen evolution reaction (HER), further improvement of their performance requires fine regulation of the TMP sites related to their specific electronic structure. Herein, for the first time, boron (B)‐modulated electrocatalytic characteristics in CoP anchored on the carbon nanotubes (B‐CoP/CNT) with impressive HER activities over a wide pH range are reported. The HER performance surpasses commercial Pt/C in both neutral and alkaline media at large current density (>100 mA cm −2 ). A combined experimental and theoretical study identified that the B dopant could reform the local electronic configuration and atomic arrangement of bonded Co and adjacent P atoms, enhance the electrons' delocalization capacity of Co atoms for high electrical conductivity, and optimize the free energy of H adsorption and H2 desorption on the active sites for better HER kinetics. Abstract : Bor auf dem Nanorohr : Die Einführung von Bor in auf Kohlenstoffnanoröhren verankerte CoP‐Nanopartikel führt zu einem robusten, pH‐universellen Katalysator für die Wasserstoffentwicklungsreaktion. Das Bor hat eine relativ niedrige Elektronegativität und verfeinert die elektronische Struktur der katalytischen CoP‐Zentren, verbessert damit die elektrische Leitfähigkeit und optimiert die freie Energie der H‐Adsorption, was zu einer verbesserten elektrokatalytischen H2 ‐Produktion führt.